Regional Strategy Paper and Regional Indicative Programme (RIP) for the period 2003-2007 ([s.n.] [S.l.], 2003)
Presents the Regional Strategy Paper including an Indicative Programme of Community Aid in favour of Cariforum which was drawn up in accordance with provisions of Articles 8 and 10 of Annex IV to the ACP-EU Partnership Agreement, signed in Cotonou on 23 June 2000.
Keywords: REGIONAL INTEGRATION